Job stress and university faculty members’ life satisfaction: The mediating role of emotional burnout - Xu, Yin; Wang, Yike (Frontiers in Psychology, 2023)
As one of the leading work-related health problems arising from the increasingly fierce competition, work-related stress has become a significant predictor for the reduced wellbeing of university faculty members, especially for those non-tenured junior ones. In light of this, this research, based on a survey, seeks to examine how and why the work-related stress casts impacts on the life satisfaction level of university junior faculty members. The results indicate that the three subdivisions of university faculty members’ work-related stress, namely research stress, teaching stress, and administrative stress, all prove to be negatively related to their life satisfaction level. In addition, emotional burnout has been confirmed to function as the underlying mechanism for the aforementioned main effects. The research contributes to the literature mainly by offering a new insight in which the three subdivisions of work-related stress are respectively regarded as independent variables affecting the life satisfaction level of university junior faculty members.